2021
DOI: 10.1037/bne0000430
|View full text |Cite
|
Sign up to set email alerts
|

The orbitofrontal cortex in temporal cognition.

Abstract: One of the most important factors in decision-making is estimating the value of available options. Subregions of the prefrontal cortex, including the orbitofrontal cortex (OFC), have been deemed essential for this process. Value computations require a complex integration across numerous dimensions, including, reward magnitude, effort, internal state, and time. The importance of the temporal dimension is well illustrated by temporal discounting tasks, in which subjects select between smaller-sooner versus large… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 140 publications
0
11
0
Order By: Relevance
“…There is also a mature literature on the neural substrates of delay discounting (Frost & McNaughton, 2017). Lesions or inactivations of brain regions such as the orbitofrontal cortex (OFC) cause animals to become intolerant of long delays before reward, and result in preferences shifting toward smaller sooner options, which would be expected to increase overstaying (Rudebeck et al, 2006; Sosa et al, 2021). There is a long history of studying sex differences in discounting (in both human and nonhuman species), and while evidence is mixed, some studies have reported sex differences in intertemporal choice paradigms (Doidge et al, 2021; Grissom & Reyes, 2019; Hernandez et al, 2020; Perry et al, 2005; Van Haaren et al, 1988; Weafer & de Wit, 2014).…”
Section: Intertemporal Choice and Impulsivitymentioning
confidence: 99%
“…There is also a mature literature on the neural substrates of delay discounting (Frost & McNaughton, 2017). Lesions or inactivations of brain regions such as the orbitofrontal cortex (OFC) cause animals to become intolerant of long delays before reward, and result in preferences shifting toward smaller sooner options, which would be expected to increase overstaying (Rudebeck et al, 2006; Sosa et al, 2021). There is a long history of studying sex differences in discounting (in both human and nonhuman species), and while evidence is mixed, some studies have reported sex differences in intertemporal choice paradigms (Doidge et al, 2021; Grissom & Reyes, 2019; Hernandez et al, 2020; Perry et al, 2005; Van Haaren et al, 1988; Weafer & de Wit, 2014).…”
Section: Intertemporal Choice and Impulsivitymentioning
confidence: 99%
“…Similarly, many forms of cognition, such as intertemporal decision-making and temporal attention also rely on timing on the scale of seconds (J. Coull & Nobre, 2008; Namboodiri et al, 2014; Nobre & van Ede, 2018; Sosa et al, 2021).…”
mentioning
confidence: 99%
“…These will, ideally, include pathway-specific manipulations to ask how each pathway contributes to the neuronal encoding downstream. These studies will have strong footing in the deep existing literature on the neuronal activity patterns of OFC and BLA Wassum and Izquierdo, 2015 ; Sharpe et al, 2019 ; Wikenheiser and Schoenbaum, 2016 ; Gardner and Schoenbaum, 2020 ; Wallis, 2011 ; O’Neill et al, 2018 ; Bissonette and Roesch, 2016 ; Salzman et al, 2007 ; Morrison and Salzman, 2010 ; Knudsen and Wallis, 2022 ; Enel et al, 2021 ; Sosa et al, 2021 ; Rich et al, 2018 ; Murray and Rudebeck, 2018 ; Averbeck and Costa, 2017 ; Sharpe and Schoenbaum, 2016 . Several exciting hypotheses have emerged from these hub recordings and the pathway-specific functional investigations described above.…”
Section: Hypotheses and Future Directionsmentioning
confidence: 86%